Characterization of GH-1 mutations in children with isolated growth hormone deficiency in the Turkish population - (:unkn) unknown (Freund Publishing House Ltd, 2009)
Isolated growth hormone deficiency (IGHD) is defined as a medical condition associated with growth failure due to insufficient production of growth hormone (GH) or lack of growth hormone action. It occurs with an incidence of between 1/4,000 and 1/10,000 live births. Most cases are sporadic and idiopathic but 5-30% of growth hormone deficiency (GHD) has genetic etiology. Mutations in the GH encoding gene (GH-1) have been detected in patients with IGHD. The purpose of this study was to characterize mutations of the GH-1 gene in children with IGHD in the Turkish population. We found four missense mutations (E33G, N47D, T-24A and A13S), one nonsense mutation (W-7X), one insertion and two deletions in nine patients out of seventy-five patients with IGHD. The missense mutation A13S, GAAA insertion at intron 1 (+178A), and the deletions of +83C in intron 1 and ΔF166 in exon 5 are novel mutations. © Freund Publishing House Ltd.
Keywords: GH-1 gene; Isolated growth hormone deficiency; Mutation analysis